(3efGgL GdHMK GdEYdGej (B/s - (3GdeRGgQI, efGd gdGds ((3GdbGgQI (B:s (3GdOGQ GdeUQjI GddHfGfjI ,s, 2015)
(3jGJj GdcJGH NWhI Ydi WQjb GdHMK GdYdej aj eLGd GdOQGSGJ GdEYdGejI h GdGSJNOGeGJ GdEMUGFjI djZWj LGfHG ef LhGfH efGgL GdHMK HeG jMhj ef ehVhYGJ eKd(B: (3YedjI GdbjGS h GfhGY GdebGjS h jJYQV GjVG ddHMhK GdcjajI h GOhGJgG GdeNJdaI s
(3HHdjhZQGajG (B: (3U(B.361-383s
Keywords: (3HMhKs; (3GdEYdGes